2017
DOI: 10.3319/tao.2016.08.26.02
|View full text |Cite
|
Sign up to set email alerts
|

Recent work on sprite spectrum in Taiwan

Abstract: This paper reports on the recent developments in spectroimagers for sprite campaigns in Taiwan. We first introduce two types of spectroimagers, the slit and slitless types, and discuss their advantages and shortcomings. Next we explore the instrument development and procedures undertaken for this study. In 2006, a slit spectroimager was installed for a sprite campaign and on 15 August of that year, two sprite spectra were recorded using the slit spectroimager along with seven sprites, one halo, one ELVES emiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(33 reference statements)
0
4
0
Order By: Relevance
“…The spectral composition of optical glow from lightning discharges (elves, sprites, etc.) mainly contains emission lines of molecular nitrogen vibration transitions lying in the red and infrared portions of the visible spectrum [Lu et al, 2017]. Changes in the chemical composition and physical conditions of the mesospherethe region of maximum development of high-altitude lightning dischargesshould have a significant effect on their parameters, therefore the research into these sporadic events is promising for the study of the upper atmosphere, space weather events, and solar-terrestrial relations.…”
Section: Introductionmentioning
confidence: 99%
“…The spectral composition of optical glow from lightning discharges (elves, sprites, etc.) mainly contains emission lines of molecular nitrogen vibration transitions lying in the red and infrared portions of the visible spectrum [Lu et al, 2017]. Changes in the chemical composition and physical conditions of the mesospherethe region of maximum development of high-altitude lightning dischargesshould have a significant effect on their parameters, therefore the research into these sporadic events is promising for the study of the upper atmosphere, space weather events, and solar-terrestrial relations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, because of the energetic proximity of these electronic excited states, the absorption/emission bands from these electronic excited states will likely lead to absorption/emission in the near-infrared and visible regions, where the JWST and Ariel space telescopes will perform observations. For example, the transitions between the two lowest-lying quartet states b 4 Σ − ↔ a 4 Π constitute what are known as the Ogawa bands [129,177], and, as far as we are aware, have not been included in theoretical radiative properties studies of air or utilized in extensive line-list calculations of NO.…”
Section: No Case Studymentioning
confidence: 99%
“…Radiative properties of heated air species are vital ingredients in detecting, modeling and characterizing many physical objects and phenomena for atmospheric science [1][2][3][4][5], exoplanets [1,[6][7][8], lightning [1,6,[9][10][11], meteoroids or vehicle (re)entry [12][13][14][15][16][17][18][19][20], electrostatic discharges or plasma Air species moles as a function of temperature along the Hugoniot of ambient air, calculated with the thermochemical code Magpie [38]. Here, a typical humidity of 35% was utilized.…”
Section: Introductionmentioning
confidence: 99%
“…Their innovative data analytical methods of nadir observation from ISS include: (1) extraction of relatively weak sprite emission from lightning emission, (2) a calculation of the intensity ratio between different photometer channels, and (3) an estimation of the charge moment change of the suspected sprite-producing CG discharge. For TLE ground campaign, Peng et al (2017) showed the first coordinated observation on TLEs from space and ground, and Lu et al (2017b) analyzed a recorded sprite spectrum by the slitless spectroimager in the 2016 Lulin Observatory ground campaign. Yang et al (2017) showed TLEs ground observations in mainland China in 2012.…”
mentioning
confidence: 99%